2014
DOI: 10.1007/s10995-013-1265-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Breastfeeding Self-efficacy Intervention: Do Hospital Practices Make a Difference?

Abstract: Breastfeeding self-efficacy interventions are important for improving breastfeeding outcomes. However, the circumstances that may influence the effectiveness of the interventions are unclear, especially in the context of hospitals with suboptimal infant feeding practices. Thus, we aimed to evaluate the effect of a self-efficacy intervention on breastfeeding self-efficacy and exclusive breastfeeding, and further assessed the difference in its effect by hospital-routine type. In this intervention study with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 27 publications
4
114
1
5
Order By: Relevance
“…We measured exclusive breastfeeding after discharge because supplementing breastfed infants is common in hospitals in Japan. 11,15 Maternal Characteristics Factors known to be associated with exclusive breastfeeding were measured in the third trimester or before discharge. These included age, [16][17][18] education level, 17,18 economic status, [16][17][18] parity, 18 marital status, 17,18 previous experience of exclusive breastfeeding for more than 3 months, 19 delivery in a BFH, 20 perceived support for breastfeeding from a partner, 16 infant's birth weight, 17,21 delivery by cesarean section, 18 returning to work within 6 months after delivery, 21 and mistimed or unwanted pregnancy.…”
Section: Infant Feeding Statusmentioning
confidence: 99%
“…We measured exclusive breastfeeding after discharge because supplementing breastfed infants is common in hospitals in Japan. 11,15 Maternal Characteristics Factors known to be associated with exclusive breastfeeding were measured in the third trimester or before discharge. These included age, [16][17][18] education level, 17,18 economic status, [16][17][18] parity, 18 marital status, 17,18 previous experience of exclusive breastfeeding for more than 3 months, 19 delivery in a BFH, 20 perceived support for breastfeeding from a partner, 16 infant's birth weight, 17,21 delivery by cesarean section, 18 returning to work within 6 months after delivery, 21 and mistimed or unwanted pregnancy.…”
Section: Infant Feeding Statusmentioning
confidence: 99%
“…Breastfeeding self-efficacy interventions are important for improving breastfeeding outcomes (34). Breastfeeding self-efficacy is mother's belief about her ability and capacity to accomplish a task or to deal with the challenges of breastfeeding (7,35,36).…”
Section: Model Goodness Of Fitmentioning
confidence: 99%
“…Furthermore, Dennis (22,23) claims that women with high breastfeeding self-efficacy will be able to control their anxiety and emotional disturbances to stay calm and respond appropriately when they need extra support. Research supports that an individual's behaviour or task performance can be influenced by their self-efficacy (20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In a randomised controlled trial of 889 Australian women, Forster, McLachlan, and Lumley (37) found a significant relationship between high breastfeeding self-efficacy scores and duration of breastfeeding at four months (λ 2 = 14.89, p <.001).…”
Section: Theory Of Self-efficacymentioning
confidence: 99%
“…Dennis (23) recommended strategies to improve women's breastfeeding self-efficacy. Some studies have used these strategies and demonstrated success in increasing woman's sense of self-efficacy; however, none of those studies were effective in promoting prolonged breastfeeding (30,32,(34)(35)(36)38).…”
Section: Theory Of Self-efficacymentioning
confidence: 99%